KONSTRUKSI DAN TEKNIK PENGOPERASIAN TAGAHU PADA PENANGKAPAN IKAN NIKE (Awaous melanocephalus) DI TELUK GORONTALO, KOTA GORONTALO - zhulmaydin chairil fachrussyah (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2019)
This study aims to describe the construction and operation of tagahu techniques in nike fishing in Gorontalo City. This research was conducted on January 5 to March 15, 2019 in Pohe Village and Leato Village in Gorontalo City, Gorontalo Province. The method used in this study is a descriptive method. The results of the study found that Tagahu is a long-shaped 4-piece jar with a pocket in the middle. Parts of the tagahu section are: 1) Main net, 2) Upper and lower Ris rope, 3) Buoy, 4) Ballast, 5) Buoy rope and Ballast Rope, 6) Capture rope, and 7) Buoy rope and Ballast Rope. The principle of Tagahu operation is generally similar to the operation of payang which is to wrap a net wing on a group of fish, then the net is pulled towards the boat. Tagahu catching can be done both at night and during the day. Tagahu's operation consists of: 1) searching of fish hordes, 2) dropping nets, 3) withdrawal and removal of nets, and 4) retrieval of catches. Keywords: Tagahu, Nets, Nike Fish